Valley filtering in strain-induced α- T3 quantum dots - Filusch, Alexander; Bishop, Alan R.; Saxena, Avadh; Wellein, Gerhard; Fehske, Holger (Physical Review B, 2021)
We test the valley-filtering capabilities of a quantum dot inscribed by locally straining an α-T3 lattice. Specifically, we consider an out-of-plane Gaussian bump in the center of a four-terminal configuration and calculate the generated pseudomagnetic field having an opposite direction for electrons originating from different valleys, the resulting valley-polarized currents, and the conductance between the injector and collector situated opposite one another. Depending on the quantum dot's width and width-to-height ratio, we detect different transport regimes with and without valley filtering for both the α-T3 and dice lattice structures. In addition, we analyze the essence of the conductance resonances with a high valley polarization in terms of related (pseudo-) Landau levels, the spatial distribution of the local density of states, and the local current densities. The observed local charge and current density patterns reflect the local inversion symmetry breaking by the strain, besides the global inversion symmetry breaking due to the scaling parameter α. By this way we can also filter out different sublattices.
CRIS-Team Scopus Importer:2021-04-30